Macroeconomic effects of loan supply shocks: Empirical evidence for Peru - Jefferson Martínez; Gabriel Rodriguez (Latin American Economic Review, 2021)
This paper quantifies and assesses the impact of an adverse loan supply (LS) shock on Peru's main macroeconomic aggregates using a Bayesian vector autoregressive (BVAR) model in combination with an identification scheme with sign restrictions. The main results indicate that an adverse LS shock: (i) reduces credit and real GDP growth by 372 and 75 basis points in the impact period, respectively; (ii) explains 11.2% of real GDP growth variability on average over the following 20 quarters; and (iii) explained a 180-basis point fall in real GDP growth on average during 2009Q1-2010Q1 in the wake of the Global Financial Crisis (GFC). Additionally,the sensitivity analysis shows that the results are robust to alternative identification schemes with sign restrictions; and that an adverse LS shock has a greater impact on non-primary real GDP growth.
Keywords: C11; E32; E51; 330; Banking System; Loan Supply Shock; Bayes-ian Autoregressive Vector Model; Sign Restrictions; Peruvian Economy